Red-Light-Induced N,N′-Dipropyl-1,13-dimethoxyquinacridinium-Catalyzed [3+2] Cycloaddition of Cyclopropylamines with Alkenes or Alkynes - Stull, Savannah M.; Mei, Liangyong; Gianetti, Thomas L. (Synlett, 2021)
A red-light-mediated [3+2] annulation of cyclopropylamines with akenes or alkynes in the presence of N,N′-dipropyl-1,13-dimethoxyquinacridinium is reported. An array of cyclopentane or cyclopentene derivatives with diverse functional groups have been obtained in moderate to excellent yields under mild conditions.
Keywords: photoredox catalysis; [3+2] cycloaddition; cyclopropylamines; alkenes; alkynes; dipropyldimethoxyquinacridinium